2019
DOI: 10.1007/978-3-030-18400-1_13
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Telecentres on the Economic Empowerment of the Youth in Disadvantaged Communities of South Africa

Abstract: We investigated how telecentres influence the economic empowerment of the youth in disadvantaged communities in South Africa and what factors affect their usage. For South Africa, the inequalities are greatly attributed to the apartheid government policy of segregating other races from major development activities. ICT is an enabler to development and may play a role in education, health and the economy. Interventions such as telecentres have the potential to deliver socioeconomic benefits for people living in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…To realize their educational goal, this is the reason why a large number of students opts to patronize the telecentres for library services as they do have the opportunity to borrow books, access audio-visual learning materials, complete school assignments and access other resources that could be supportive to their educational goals. The findings are in agreement with Booi, Chigona, Maliwichi and Kunene, (2019) who reported that telecentres in South Africa were fully packed with children from primary and secondary schools on weekends and in the afternoon of weekdays to obtain school materials and use library books and other resources. Telecentre library services, provide users with materials that improve their knowledge and academic achievement (Kapondera & Namusanya, 2017).…”
Section: Limited Space Within Telecentressupporting
confidence: 92%
See 4 more Smart Citations
“…To realize their educational goal, this is the reason why a large number of students opts to patronize the telecentres for library services as they do have the opportunity to borrow books, access audio-visual learning materials, complete school assignments and access other resources that could be supportive to their educational goals. The findings are in agreement with Booi, Chigona, Maliwichi and Kunene, (2019) who reported that telecentres in South Africa were fully packed with children from primary and secondary schools on weekends and in the afternoon of weekdays to obtain school materials and use library books and other resources. Telecentre library services, provide users with materials that improve their knowledge and academic achievement (Kapondera & Namusanya, 2017).…”
Section: Limited Space Within Telecentressupporting
confidence: 92%
“…Previous studies revealed that telecentres act as centres where people are equipped with ICT skills and knowledge through the provision of computer lessons and digital literacy skills that prepares users for job opportunities (Attwood et al, 2013; Kapondera & Namusanya, 2017). According to Booi et al (2019), youth in underprivileged communities could not manage to pay for ICT training, therefore free training sessions offered by the telecentres would be beneficial. The telecentres play an important role in promoting digital citizenship in poor populations through ICT training that is provided in rural areas (Breitenbach, 2013).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
See 3 more Smart Citations